2018
DOI: 10.3389/fmicb.2018.02053
|View full text |Cite
|
Sign up to set email alerts
|

Toward Integrative Bacterial Monitoring of Metolachlor Toxicity in Groundwater

Abstract: Common herbicides such as metolachlor (MET), and their transformation products, are frequently detected in groundwater worldwide. Little is known about the response of groundwater bacterial communities to herbicide exposure, and its potential use for ecotoxicological assessment. The response of bacterial communities exposed to different levels of MET from the Ariège alluvial aquifer (Southwest of France) was investigated in situ and in laboratory experiments. Variations in both chemistry and bacterial communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 55 publications
2
12
0
Order By: Relevance
“…Moreover, as mentioned above, microbial community diversity as well as the history of pesticide contamination (i.e., communities previously in contact or not with pesticides) can influence the impact of pesticides. Finally, the work of Imfeld et al (2018) also suggested a little effect of metolachlor on in situ bacterial groundwater community (Microtox test and T-RFLP fingerprints). In this same work, the transformation products of S-metolachlor (as ESA and OXA-metolachor) were shown to have no effect on microbial metabolism.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Moreover, as mentioned above, microbial community diversity as well as the history of pesticide contamination (i.e., communities previously in contact or not with pesticides) can influence the impact of pesticides. Finally, the work of Imfeld et al (2018) also suggested a little effect of metolachlor on in situ bacterial groundwater community (Microtox test and T-RFLP fingerprints). In this same work, the transformation products of S-metolachlor (as ESA and OXA-metolachor) were shown to have no effect on microbial metabolism.…”
Section: Discussionmentioning
confidence: 92%
“…This last point is not in agreement with our results that showed no impact of the tested pesticides on the relative abundance of the nitrate reductase narG and napA genes involved in the first step of denitrification. One explanation is probably that the data of Mauffret et al (2017) were obtained from in situ groundwater, whereas our results concern batch experiments, and it has been demonstrated that for in situ studies particularly, there are difficulties to tease apart the effect of pesticides from the effects of variations of hydrogeological conditions ( Imfeld et al, 2018 ). Moreover, as mentioned above, microbial community diversity as well as the history of pesticide contamination (i.e., communities previously in contact or not with pesticides) can influence the impact of pesticides.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations